2017
DOI: 10.1039/c6ra28392f
|View full text |Cite
|
Sign up to set email alerts
|

Polyolefin/graphene nanocomposites: a review

Abstract: Polymeric materials reinforced with nanofillers continue to fulfill the worldwide demand for alternative materials with low cost and better physico-mechanical properties. These materials are prepared by mixing polymers with nanofillers (e.g. layered silicates, metal oxides, carbon nanotubes (CNTs) and graphene) using in situ or melt blending techniques for improved physico-mechanical properties. Among all the nanofillers, CNTs and graphene have emerged as subjects of tremendous scientific interest and have att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 113 publications
(122 reference statements)
3
82
1
Order By: Relevance
“…However, it could be associated with the existence of a multi-step percolation behavior where a tunneling mechanism dominates the current flow between the conductive particles [46,55]. Most importantly, the percolation threshold reported in this study is significantly lower than those reported previously for polypropylene [40,41,56] using melt mixing methods [27] and other similar polymers [57]. An overview of the reported electrical percolation values for a number of different polypropylene/graphene systems prepared with various melt mixing protocols is presented in Table 1.…”
Section: Electrical Conductivitymentioning
confidence: 55%
“…However, it could be associated with the existence of a multi-step percolation behavior where a tunneling mechanism dominates the current flow between the conductive particles [46,55]. Most importantly, the percolation threshold reported in this study is significantly lower than those reported previously for polypropylene [40,41,56] using melt mixing methods [27] and other similar polymers [57]. An overview of the reported electrical percolation values for a number of different polypropylene/graphene systems prepared with various melt mixing protocols is presented in Table 1.…”
Section: Electrical Conductivitymentioning
confidence: 55%
“…Different conductive particles have been investigated as fillers for these composites such as metallic particles and carbon based particles including carbon fibers, carbon black, carbon nanotubes, reduced graphene oxide, exfoliated graphite and graphene [3][4][5][11][12][13][14][15][16]. In particular, graphene gained increasing interest recently, to be used as an effective filler in polymer composites to enhance their electrical, thermal and mechanical properties, due to its outstanding intrinsic properties, low density and very attractive geometry, i.e., high aspect ratio, high effective surface area and plate-like geometry [10,12,[17][18][19]. However, one of the current challenges is the production of cost-effective graphene nanoplatelets at a large industrial scale This is the author's peer reviewed, accepted manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved either by using special processing techniques, functionalization of the polymer matrix or the particles, and/or selection of a multiphase polymer matrix as a template for controlled dispersion [11,12,[20][21][22][23]. As far as the two first options are concerned, versatile and successful techniques leading to low and even ultra-low values of percolation threshold have been reported in literature [5,11,19,[24][25][26][27]. However, the involved processing methods and chemical modifications are often complex and not scalable while the use of industrial techniques is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident from the large number of research publications. Graphene-based nanocomposites have been prepared with a number of polymer matrices including polyvinyl alcohol(PVA) [5,13], poly ethylene (PE) [4,14], poly propylene(PP) [15], poly styrene (PS) [16], polyamide [17], poly urethane (PU) [18], poly imide (PI) [11,19], polyvinyl chloride (PVC) [20,21], poly carbonate(PC) [22], elastomers [23,24], and so forth. Most of these composites have been made by solution mixing and casting method.…”
mentioning
confidence: 99%